Recent developments in luminescent coordination polymers: Designing strategies, sensing application and theoretical evidences - Liu J.-Q.; Luo Z.-D.; Pan Y.; Kumar Singh A.; Trivedi M.; Kumar A. (My University, 2025)
The designing, characterization and utility of luminescent coordination polymers as sensors to detect molecules and ions, constitute an active area of research. Further, theoretical investigation on these systems using variety of wave functions add new flavor in providing better understanding of the electronic properties of the coordination polymers causing selectivity in sensing. The coordination polymers offer unique luminescence and electronic properties owing to interplay of electron density between the metal centers and organic ligands. The related electronic properties of coordination polymers can be regulated by changing their chemical structures which in turn can be controlled by amending the metal–ligand interaction at molecular level. The presented review focuses on the general introduction of coordination polymers in particular laying stress on the advancement of luminescent coordination polymers incorporating rare-earth, transition and alkaline earth metals for sensing technology applications. Additionally, computational investigation in the detection of nitroaromatic explosives, organic solvents, metal ions have been presented and uses of luminescent coordination polymers as sensors for pH, water, oxygen, H2S, glucose, amino acids have also been mentioned. © 2019 Elsevier B.V.